Evidence-Based Nursing: Management of Radial Access Complications Post PCI - Ali, Abda; Anshar, Rizadin (Newinera Publisher, 2025)
The advancement of interventional cardiology technology has enhanced the effectiveness of patient care for coronary artery disease, particularly through Percutaneous Coronary Intervention (PCI) using radial access. Although this approach is safer than femoral access, post-procedural complications such as hematoma, radial artery occlusion, and neuropathy remain clinical challenges. Evidence-Based Nursing Management plays a crucial role in minimizing the risk of complications through evidence-based interventions, including nurse education, optimization of compression techniques, and rehabilitation strategies. This study aims to analyze research trends related to evidence-based management in addressing post-radial PCI complications using bibliometric analysis with VOSviewer. The methodology includes a systematic literature review following the PRISMA protocol and bibliometric analysis of publications from 2020 to 2025 sourced from Google Scholar, ScienceDirect, and Wiley Online Library. The analysis results highlight emerging research trends in post-radial PCI complication management, identification of research gaps, and evidence-based policy recommendations. This study contributes to strengthening evidence-based nursing practices to enhance patient safety and care efficiency in PCI procedures.